Flash sintering of silicon carbide with boron and carbon sintering aids - Gibson, AR (2023)
The aims of this doctoral thesis were to assess the feasibility of using flash sintering to manufacture silicon carbide and to understand how the technique affects its density, microstructure and mechanical properties.